Comparative study of infrastructure development and its impact on human development index: Economic and geographical insights - Syam, Ibnu Hafizh (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Urban-focused development can lead to disparities in infrastructure and transportation development. The lack of adequate infrastructure causes many people to live isolated in remote areas, hindering their access to resources and basic services. Methods: This contributes to high poverty levels and low human development in those regions. The absence of infrastructure results in many communities being trapped in impoverished, remote areas, making it essential to open access to facilitate development. Findings: The Human Development Index (HDI) is an important indicator to ensure the achievement of the goal that people have a good quality of life, including the ability to live healthily and for a long time, access education, gain knowledge, and have access to employment opportunities, social protection programs, and other resources needed to achieve a decent life. The acceleration of HDI growth in 2023 is partly driven by the standard of living dimension, represented by real per capita expenditure, health (life expectancy at birth), and knowledge (average years of schooling and expected years of schooling). Conclusion: To achieve sustainable and just development, infrastructure is needed to improve accessibility and connectivity between regions to encourage economic growth and community well-being. Novelty/Originality of this article: This study highlights the critical role of infrastructure in reducing regional disparities and accelerating human development, emphasizing its impact on HDI growth—an aspect often overlooked in previous research.